PENGARUH PENGETAHUAN PRODUK DAN LIFESTYLE TERHADAP MINAT BELI PRODUK CREAM GLOW & LOVELY DI KOTA BIMA - Nurul Magfirah; Kartin Aprianti (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of product knowledge and lifestyle on purchase intention of cream glow & lovely in Bima City. The approach used in this research is using an associative approach. The sample in this study was 96 respondents. The data collection techniques used were observation, questionnaires, and literature study. Data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, coefficients of determination, t tests, and F tests processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results showed that product knowledge (X1) and lifestyle (X2) partially and simultaneously have a significant effect on the interest in buying cream glow & lovely products in Bima City with an effect of 56.8%.